Let's go to the zoo - Bernthal;Mark (New Delhi Scholastic Inc, 2001)
The book introduces readers to various zoo animals through vibrant illustrations and simple, engaging text. It typically features a friendly guide or a character that leads the reader through different zoo exhibits, showcasing a variety of animals such as lions, elephants, monkeys, and giraffes.